Identification of Transcriptomic Differences in Induced Pluripotent Stem Cells and Neural Progenitors from Amyotrophic Lateral Sclerosis Patients Carrying Different Mutations: A Pilot Study - Chiara Sgromo; Martina Tosi; Cristina Olgasi; Fabiola De Marchi; Francesco Favero; Giorgia Venturin; Beatrice Piola; Alessia Cucci; Lucia Corrado; Letizia Mazzini; Sandra D’Alfonso; Antonia Follenzi (Cells)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease affecting motor neurons with a phenotypic and genetic heterogeneity and elusive molecular mechanisms. With the present pilot study, we investigated different genetic mutations (C9orf72, TARDBP, and KIF5A) associated with ALS by generating induced pluripotent stem cells (iPSCs) from peripheral blood of ALS patients and healthy donors. iPSCs showed the typical morphology, expressed stem cell markers both at RNA (OCT4, SOX2, KLF4, and c-Myc) and protein (Oct4, Sox2, SSEA3, and Tra1-60) levels. Moreover, embryoid bodies expressing the three germ-layer markers and neurospheres expressing neural progenitor markers were generated. Importantly, the transcriptomic profiles of iPSCs and neurospheres were analyzed to highlight the differences between ALS patients and healthy controls. Interestingly, the differentially expressed genes (DEGs) shared across all ALS iPSCs are linked to extracellular matrix, highlighting its importance in ALS progression. In contrast, ALS neurospheres displayed widespread deficits in neuronal pathways, although these DEGs were varied among patients, reflecting the disease’s heterogeneity. Overall, we generated iPSC lines from ALS patients with diverse genetic backgrounds offering a tool for unravelling the intricate molecular landscape of ALS, paving the way for identifying key pathways implicated in pathogenesis and the disease’s phenotypic variability.